GREEN INDUSTRIAL POLICY: A DELICATE DANCE BETWEEN SOCIO-ECONOMIC AND ENVIRONMENTAL OBJECTIVES - Narassimhan, Easwaran. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: Kelly Gallagher.; Committee: Navroz Dubash, and Bhaskar Chakravorti.; Keywords: International relations, Public policy, and Climate change.